(untitled) (Journal of Applied Learning and Teaching, 2022)
Due to the logistic and interpersonal demands of applied teaching, applied educators often simultaneously have more to meet about and less time available for meetings. This can contribute to time poverty and overwhelm in a cycle that erodes productivity over time. While meetings are often necessary, they are frequently inefficient, ineffective, and demoralizing. This paper reviews relevant studies on effective meeting redesign, recommends specific strategies for applied academics, and describes an example of implementation in an applied learning setting.